2013
DOI: 10.1177/193229681300700518
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Evaluation of a New Glucose Meter System in 15 Different Critical Care Settings

Abstract: Background: Maintaining appropriate glycemic control in critically ill patients reduces morbidity and mortality. The use of point-of-care (POC) glucose devices is necessary to obtain rapid results at the patient's bedside. However, the devices should be thoroughly tested in the intended population before implementation. The use of POC glucose meters in critically ill patients has been questioned both in the literature and by regulatory agencies. The aim of this study was to determine if the ACCU-CHEK ® Inform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Overall our results confirm previous reports [16][17][18][19][20][21]. Using the 10% criterion recently set forward by the FDA [12], only for the BGA all results fell within these boundaries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall our results confirm previous reports [16][17][18][19][20][21]. Using the 10% criterion recently set forward by the FDA [12], only for the BGA all results fell within these boundaries.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies tested meters in populations not limited to critically ill patients [16][17][18][19][20][21] or in neonatal populations focusing on detection of hypoglycemia [17,18,20], and weighted results not [16,19,20] or per less stringent CLSI or ISO 15197 criteria [17,18,21], or used the glucose oxidase method [18,20,21] instead of the more definitive [22] coupled hexokinase -glucose-6-phosphate dehydrogenase (HK/G6PD) method [16,17,19]. In the present study we compared three hospital-type handheld strip-based systems on whole blood samples of our surgical intensive care unit (ICU), with our blood gas analyzer (BGA) and with the central laboratory HK/G6PD method.…”
Section: Introductionmentioning
confidence: 99%
“…Newer meter technologies may provide more accurate glucose measurement 1214 when used on critically ill patients, though studies have not specifically addressed capillary sampling or use of meters intraoperatively. One previous study 33 specifically examined glucose measurements in the OR, although few patients were under anesthesia at the time of sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Though newer technologies may provide more accuracy 1214 , there is still concern about the use of meters in the critically ill 15,16 . Studies have demonstrated potentially dangerous discrepancies in capillary glucose measurement in patients on vasopressor therapy 10,17 , patients in shock 18 or with poor tissue perfusion 19 , and in other critically ill patient populations 20 .…”
Section: Introductionmentioning
confidence: 99%
“…To date serum glucose tight control is recommended to avoid both hypo-and hyper-glycaemia, according to the NICE-SUGAR trial, the best study on glycemic control strategies among ICU patients (10). There is now general consensus about glycemic management of criticallyill patients; guidelines recommend to maintaining blood glucose lower than 180 mg/dL (11).…”
Section: Resultsmentioning
confidence: 99%